Notes on the life history of Aguna megacles megacles (Mabille, 1888) (Lepidoptera: Hesperiidae: Eudaminae) feeding on Bauhinia species in the State of Alagoas, Brazil - Suênia-Bastos, Ayane; Cajé, Suianne O. S.; Duarte-de-Mélo, Jefferson; M. M. Lima, Iracilda (Instituto de Ecología, A.C., 2021)
Eudaminae Mabille, 1877 (Hesperiidae), recognized as subfamily recently, is rich in Brazil. It is along the Neotropical Region where a significant part of the diversity is found, however, information that involves the biology of species is poorly yet. This paper gathers new bioecological data of an Aguna species from the municipality of Maceió (Alagoas, Brazil), close to the Environmental Protection Area of “Catolé” and “Fernão Velho”, a remnant of Atlantic Forest. Leaves containing eggs were collected in a peri-urban area (9° 33’ 26” S, 35° 46’ 36” W) and taken to laboratory to observe post-embryonic development. Larvae were also collected from another host plant in an intra-urban area (9° 39’ 40” S, 35° 41’ 58” W). The specimens were identified as Aguna megacles megacles (Mabille, 1888) and the two Fabaceae as Bauhinia pentandra (Bong.) D. Dietr. and Bauhinia monandra Kurz. from exsiccates deposited at the Herbarium. Rearing from the eggs collected on B. pentandra exposes a post-embryonic development that lasted 53.4 days for six larval instars individuals, and 46 days for the five larval instars specimen. The larvae built a shelter since the first instar and in laboratory conditions they preferred pupate on the base of the cage. This is the first report of development features for A. m. megacles, including six and five larval instars, as well as a new locality for the State of Alagoas, and two more host plants of Bauhinia suggesting specialist behavior.